Early Implementation of a Family-Centred Practice Model in Child Welfare: Findings from an Irish Case Study. Issue 5 (20th October 2017) - Devaney, Carmel; McGregor, Caroline; Cassidy, Anne
Abstract : This article reports on the outcomes of a research study on the early implementation of a strengths-based family-centred model of practice in Ireland known as the Meitheal model. The paper aims to translate the key messages from this research to practice with families involved in the child welfare system. This is done by highlighting the process by which intervention focused on support and prevention using a strengths perspective has begun to occur in practice. Using data collected from stakeholders involved in the implementation of the practice model, the research provides insight into the opportunities and challenges involved at macro and micro-levels of practice. The discussion links this development in Ireland to the wider international context, using three broad frameworks informed by the ecological model; a framework for determining thresholds in children's services and the continuum of intervention between support and protection to inform system change aimed at enhancing family support and better outcomes for children and families. Underpinning this is an emphasis on how Meitheal as a strengths-based approach can influence the achievement of the principles of early intervention, prevention and family support in the child welfare system in Ireland.